Privatization and the arrangement of city services - Stein, Robert (Estudios de Economía, 2016)
Contemporary research on service delivery has been preoccupied with the issue of privatization. Specifically, the concern has been with whether a governmental or non governmental entity is more effective and efficient in delivering publicly provided goods and services. In this paper I offer and alternative perspective on service delivery which examines the full array of institutional arrangements used by municipal governments to deliver different goods and services. I relate these choices to characteristics of individual goods and services and derive a simple thesis. The way governments arrange for service delivery is a function of the scope and content of their service responsibilities. Different goods and services are more effectively and efficiently provided by different modes of service arrangement. The question is not whether one sector is more widely used than another, but rather whether governments have effectively matched their service responsibilities with the appropriate method of service arrangement.